"Hahaha technique": an easy way to write a press release / Abdul Hamid Saifuddin, Mohd Yusof Zulkefli and Wardatul Hayat Adnan - Saifuddin, Abdul Hamid; Zulkefli, Mohd Yusof; Adnan, Wardatul Hayat (Universiti Teknologi MARA, Kedah, 2023)
Journalists and media outlets have far more reach than a business alone. Hence using press releases to garner more attention and awareness makes sense. An effective press release is also an excellent way to control how the business is viewed. An organisation can build their brand image and shape public perception through an informative official statement with facts to counter any negative publicity. However, there is a plethora of press release examples that can be viewed and searched online. Unfortunately, choosing the best example cannot be very clear because there are many writing styles. Hence, the "hahaha technique" has been introduced and used effectively as a teaching aid in the PRO450 Media Release course from the Faculty of Communication and Media Studies, Universiti Teknologi MARA. By utilising the element of one paragraph consisting of two sentences within four lines, this technique has also helped many other corporate executives from different departments in UiTM to write constructive press releases. Besides, "hahaha techniques" also bold the element of introduction, reason or objective, reciprocal, humanistic touch and context within five paragraphs, enabling everyone to write a press release efficiently. Sending press releases is a mutually beneficial exercise. Journalists need stories. Hence, a press release could start a relationship with someone in the media industry.